Editorial - Solihu, Abdul Kabir Hussain (IIUM Press, 2014)
During periods of social, political or economic discontent leading to communal unrest, people tend to turn against established social patterns in search of saviours to ameliorate their sufferings and restore order. For believing communities, such as the Muslim community, recourse has been made to religion in the hope of enjoying what the Qur’ān calls “ḥayātan ṭayyibah” (a good and prosperous life) promised to those who uphold its values. The vanguards of transformation who are the torchbearers in Islamic religious thought are known as revivalists or reformers. Their regenerative activities are often described as iṣlāḥ (reform), iḥyā’ (revival), tajdīd (renewal), or ṣaḥwah (awakening), among others. Among the prominent early Muslim reformers are al-Ghazālī (d. 1111), Ibn Taymiyyah (d. 1328), and Ibn Khaldūn (d. 1406). Shah Walī Allāh al-Dihlawī (d. 1762), Muhammad ibn ‘Abd al-Wahhāb (d. 1792), Uthman dan Fodio (d. 1817), and Ahmad ibn Idris (d. 1837) are among the well-known reformers of the eighteenth and nineteenth centuries (Rahman, 1970; Voll, 1999). These individuals or movement leaders differed in their approaches; yet their primary concern, as Fazlur Rahman observes, was with the socio-moral reform and reconstruction of Muslim societies based on the values promoted in the Qur’ān and Sunnah (Rahman, 1970, p. 640).